Strategies for enhancing the accuracy and security in ad hoc networks - Delijani, Behnam Rahmani; Tavakoli, Hassan (Journal of Advanced Computer Science & Technology, 2015)
Ad Hoc networks are a type of mobile wireless networks composed of mobile and stationary nodes which are moving freely and independently or they are stable. Setting up Ad Hoc networks is very simple and as these networks do not need a standard fixed infrastructure and central legal license, their setting up cost is very low. So, in specials, temporary or short-term situations such as flood, earthquake and fire as well as in military environments where all telecommunication platforms are destroyed, these networks are used as a new solution for creating communications between network elements. As Ad Hoc networks have a limited energy and nodes are continuously displacing, consequently, the accuracy of these networks is important. Nodes can be easily added to the network at any time or leave the network. It not only leads to easy creation of a network and its fast, easy and low-cost expansion, but also makes it possible for an enemy to enter the network. Therefore, the security of these networks must also be considered. In this paper, using a new method and imposing limitations on some network nodes, we created a more reliable network with higher accuracy and security.